2015
DOI: 10.1111/iji.12190
|View full text |Cite
|
Sign up to set email alerts
|

Imputation of class I and II HLA loci using high‐density SNPs from ImmunoChip and their associations with Kawasaki disease in family‐based study

Abstract: Summary Kawasaki disease (KD) is the leading cause of acquired heart disease in children in most developed countries including the United States. The etiology of KD is not known; however, epidemiological and immunological data suggest infectious or immune-related factors in the manifestation of the disease. Further, KD has several hereditary features that strongly suggest a genetic component to disease pathogenesis. Human leukocyte antigen (HLA) loci have also been reported to be associated with KD but results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Viral-like inclusion bodies were found in the lungs of this patient similar to findings in other patients with KD and supporting an underlying viral etiology [7]. Increasing evidence suggests that an individual's immune response to the inciting event or pathogen, as determined by their genetic background, exerts a significant influence on the severity of presentation and responsiveness of the illness to IVIG [8,9]. As the era of personalized medicine gains support, inflammatory diseases such as KD may benefit from the development of tools to precisely define the risk for severe/refractory disease, and allow practitioners to tailor treatment regimens with better precision.…”
Section: Discussionsupporting
confidence: 77%
“…Viral-like inclusion bodies were found in the lungs of this patient similar to findings in other patients with KD and supporting an underlying viral etiology [7]. Increasing evidence suggests that an individual's immune response to the inciting event or pathogen, as determined by their genetic background, exerts a significant influence on the severity of presentation and responsiveness of the illness to IVIG [8,9]. As the era of personalized medicine gains support, inflammatory diseases such as KD may benefit from the development of tools to precisely define the risk for severe/refractory disease, and allow practitioners to tailor treatment regimens with better precision.…”
Section: Discussionsupporting
confidence: 77%
“…We find that SNP2HLA generated high confidence imputation at one- and two-field resolution which was validated by SSP-based direct HLA typing for 5 loci. Imputation of HLA alleles and amino acid polymorphisms using SNP2HLA has been successfully implemented for genetic studies of associations in a range of traits [44], [45], [46], [47], [48].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our findings revealed a novel pathogenic effect of HLA-C molecules, which can be exerted by leucine at amino-acid position 116 in the middle of the epitope-binding site. This residue was correlated with one of the HLA-C*15 alleles that have been suggested to be associated with Kawasaki disease, Behçet’s disease, and leprosy [ 15 17 ]. However, because this study had no replication cohort and previous European studies have not reported the association for HLA-C amino-acid position 116, this association needs to be validated in an independent cohort in the future.…”
Section: Discussionmentioning
confidence: 99%